A Genetic Dissection of Natural Variation for Stomatal Abundance Traits in Arabidopsis - Delgado, Dolores; Sánchez-Bermejo, Eduardo; de Marcos, Alberto; Martín-Jimenez, Cristina; Fenoll, Carmen; Alonso-Blanco, Carlos; Mena, Montaña (Frontiers in Plant Science, 2019)
Stomatal abundance varies widely across natural populations of Arabidopsis thaliana, and presumably affects plant performance because it influences water and CO2 exchange with the atmosphere and thence photosynthesis and transpiration. In order to determine the genetic basis of this natural variation, we have analyzed a recombinant inbred line (RIL) population derived from the wild accession Ll-0 and the reference strain Landsberg erecta (Ler), which show low and high stomatal abundance, respectively. Quantitative trait locus (QTL) analyses of stomatal index, stomatal density and pavement cell density measured in the adaxial cotyledon epidermis, identified five loci. Three of the genomic regions affect all traits and were named MID (Modulator of Cell Index and Density) 1 to 3. MID2 is a large-effect QTL overlapping with ERECTA (ER), the er-1 allele from Ler increasing all trait values. Additional analyses of natural and induced loss-of-function er mutations in different genetic backgrounds revealed that ER dysfunctions have differential and opposite effects on the stomatal index in adaxial and abaxial cotyledon epidermis and confirmed that ER is the gene underlying MID2. Ll-0 alleles at MID1 and MID3 displayed moderate and positive effects on the various traits. Furthermore, detailed developmental studies tracking primary and satellite stomatal lineages show that MID3-Ll-0 allele promotes the spacing divisions that initiate satellite lineages, while the ERECTA allele limits them. Finally, expression analyses suggest that ERECTA and MID3 modulate satellization through partly different regulatory pathways. Our characterization of MID3 indicates that genetic modulation of satellization contributes to the variation for stomatal abundance in natural populations, and subsequently that this trait might be involved in plant adaptation.